Heavy metal accumulation and health risk assessment in wastewater-irrigated urban vegetable farming sites of Addis Ababa, Ethiopia - Woldetsadik, D.; Drechsel, Pay; Keraita, Bernard N.; Itanna, F.; Gebrekidan, H. (Springer, 2017)
Background: Wastewater irrigation for vegetable production is a highly prevalent practice in Addis Ababa and a number of articles have been published on wastewater-irrigated soils and vegetables contaminated with heavy metals. However, to the best of our knowledge, an insight into assessment of human health risks associated with the consumption of vegetable crops grown on wastewater-irrigated soils is non-existent in the city. Long-term effect of wastewater irrigation on the build-up of heavy metals in soils and selected vegetable crops in Addis Ababa urban vegetable farming sites (10) was evaluated. By calculating estimated daily intakes (EDIs) and target hazard quotients (THQs) of metals, health risk associated with the consumption of the analyzed vegetables was also evaluated. Results: The heavy metal concentrations in irrigation water and soils did not exceed the recommended maximum limits (RMLs). Moreover, Cd, Co, Cr, Cu, Ni and Zn concentrations in all analyzed vegetables were lower than the RML standards. In contrast, Pb concentrations were 1.4–3.9 times higher. Results of two way ANOVA test showed that variation in metals concentrations were significant (p < 0.001) across farming site, vegetable type and site x vegetable interaction. The EDI and THQ values showed that there would be no potential health risk to local inhabitants due to intake of individual metal if one or more of the analyzed vegetables are consumed. Furthermore, total target hazard quotients (TTHQs) for the combined metals due to all analyzed vegetables were lower than 1, suggesting no potential health risk even to highly exposed local inhabitants. Conclusions: There is a great respite that toxic metals like Pb and Cd have not posed potential health risk even after long term (more than 50 years) use of this water for irrigation. However, intermittent monitoring of the metals from irrigation water, in soil and crops may be required to follow/prevent their build-up in the food chain.